The influence of brand image on Chinese consumers’ decision-making process in the smartphone market - Zhang, Danye (2019)
In recent years, the Chinese mobile phone market has grown rapidly, showing the diversification of brands and products. With the increased competition, economic downturn and the reduced frequency of consumers changing mobile phones, mobile phone brands that are not favored by consumers are gradually being eliminated from the market. However, the well-known mobile phone brands have gained the trust of consumers and ushered in rising market share and influence. Therefore, understanding and exploring which dimension in the brand image will promote consumers to buy mobile phones, and how the brand image affects the consumer’s decision-making process is crucial for the company to achieve its development goals and long-term operations. Simultaneously, it can provide theoretical and practical guidance for companies to build a strong brand image.